Master and Servant Love and Labour in the English Industrial Age - Steedman, Carolyn (Cambridge University Press, 2013)
This is a book about one servant and one master and the changing shape of their relationship, lived out in the time and place of the ‘making of the English working class’, the industrial West Riding of Yorkshire. It covers the period from about 1785 when Phoebe Beatson first came to the service of the Reverend John Murgatroyd of Slaithwaite, just outside Huddersfield, to the first decade of the new century, after she had borne her illegitimate child, scandalously, in a clergyman’s house. The Anglican God whom Murgatroyd served and promoted throughout his very long life changed His shape and form during these years of war, dearth, revolution and counter-revolution; church and state, the law and its practice, redefined the service relationship, and the human and social relationship ‘service’ inscribed. Here, in what follows, we have one tiny birth pang of modern, industrial society, and some of the minute shifts and stratagems of feeling that countless individuals undertook, in making themselves subjects of modernity.